Effect of Cutting Date and Seed Rate on the Productivity of Green Fodder and Grains of Oat Crop (Avena sativa L.) (Journal of Hama University, 2025)
This research was conducted during the 2021/2022 agricultural season at Bouqa Farm in Lattakia to study the effect of cutting dates and seed rates on the productivity of green fodder and oat grains for dual-purpose use. The Syrian cultivated oat variety was used. Cutting was performed in two stages: at the tillering stage and then at the stem elongation stage, with a control treatment of no cutting. Three seed rates (100, 140, 180 kg/ha) were also tested. The experiment was executed using a randomized complete block design with three replications. The results showed a significant effect of cutting date and seed rate on the productivity and its components of the oat crop: The no-cutting treatment excelled in the number of tillers/m², the number of panicles/m², and the number of grains per panicle, which positively reflected on the grain yield, reaching (3211 kg/ha). The cutting treatment at the stem elongation stage achieved the highest green fodder yield, reaching (3283.6 kg/ha). Using a seed rate of 180 kg/ha showed a significant increase in grain yield, which reached (3191 kg/ha). The seed rates of 140 and 180 kg/ha recorded the best green fodder yields, reaching (3033.5 and 3246.3 kg/ha) respectively. The interaction between the no-cutting treatment and the 180 kg/ha seed rate achieved the highest grain yield, reaching (3686 kg/ha). Cutting the plants at the stem elongation stage with a 180 kg/ha seed rate led to the highest green fodder yield, reaching (3484 kg/ha).
Keywords: Oat; productivity; green fodder; grains; cutting date; seed rate